Preclinical Development of New Therapy for Glycogen Storage Diseases - Sun, Baodong (Curr Gene Ther, 2015)
Glycogen storage disease (GSD) consists of more than 10 discrete conditions for which the biochemical and genetic bases have been determined, and new therapies have been under development for several of these conditions. Gene therapy research has generated proof-of-concept for GSD types I (von Gierke disease) and II (Pompe disease). Key features of these gene therapy strategies include the choice of vector and regulatory cassette, and recently adeno-associated virus (AAV) vectors containing tissue-specific promoters have achieved a high degree of efficacy. Efficacy of gene therapy for Pompe disease depend upon the induction of immune tolerance to the therapeutic enzyme. Efficacy of von Gierke disease is transient, waning gradually over the months following vector administration. Small molecule therapies have been evaluated with the goal of improving standard of care therapy or ameliorating the cellular abnormalities associated with specific GSDs. The receptor-mediated uptake of the therapeutic enzyme in Pompe disease was enhanced by administration of β2 agonists. Rapamycin reduced the liver fibrosis observed in GSD III. Further development of gene therapy could provide curative therapy for patients with GSD, if efficacy from preclinical research is observed in future clinical trials and these treatments become clinically available.